Biology and diseases of the ferret - Fox, James G.; Marini, Robert P.; Wiley eBooks (Ames, Iowa : John Wiley & Sons Inc., 2014)
Biology and Diseases of the Ferret, Third Edition has been thoroughly revised and updated to provide a current, comprehensive reference on the ferret. Encyclopedic in scope, it is the only book to focus on the characteristics that make the ferret an important research animal, with detailed information on conditions, procedures, and treatments. Offering basic information on biology, husbandry, clinical medicine, and surgery, as well as unique information on the use of ferrets in biomedical research, Biology and Diseases of the Ferret is an essential resource for investigators using ferrets in.
Taxonomy, history and use / James G. Fox -- Anatomy of the ferret / Howard Evans and Nguyen Quoc An -- Neuroanatomy of the ferret brain / Christopher D. Kroenke, Brian Mills, Jaime F. Olavarria, and Jeffrey J. Neil -- Physiology of the ferret / Mark T. Whary -- Nutrition / James G. Fox, Carrie S. Schultz, and Brittany M. Vester Boler -- Housing and management / James G. Fox and Rosemary Broome -- Normal clinical and biological parameters / James G. Fox -- Growth, reproduction and breeding / James G. Fox, Judi Bell, and Rosemary Broome -- Regulatory considerations / Robert P. Marini -- Black-footed ferret recover / Rachel Santymire, Heather Branvold-Faber, and Paul Marinari -- Physical examination and diagnosis / Robert P. Marini -- Anesthesia / Jeffrey Ko and Robert P. Marini -- Surgery / Stephen J. Mehler and Robert P. Marini -- Hematopoietic diseases / Jerg Mayer, Susan E. Erdman, and James G. Fox -- Diseases of the genitourinary tract / James G. Fox and Judi Bell -- Diseases of the gastrointestinal system / Kirk J. Maurer and James G. Fox -- Diseases of the endocrine system / Cassandra L. Miller, Robert P. Marini, and James G. Fox -- Diseases of the cardiovascular system / Robert A. Wagner -- Other systemic diseases / James G. Fox -- Viral diseases / Matti Kuipel and David Perpiñan -- Bacterial and mycoplasmal diseases / Alton G. Swennes and James G. Fox -- Parasitic diseases / Mary Patterson, James G. Fox, and Mark L. Eberhard -- Mycotic diseases / James G. Fox -- Neoplastic diseases / James G. Fox, Sureshkumar Muthupalani, Matti Kiupel, and Bruce Williams -- The ferret in viral respiratory disease research / Deborah R. Taylor -- The ferret in morbillivirus research / Veronika von Messling -- Use of the ferret in cardiovascular research / James P. Morgan -- Genetic engineering in the ferret / Xingshen Sun, Ziying Yan, Xiaoming Liu, Alicia K. Oliver, and John F. Engelhardt -- Hearing and auditory function in ferrets / Fernando R. Nodal and Andrew J. King -- The ferret in vision and neuroplasticity research / Jitendra Sharma and Mriganka Sur -- The ferret in nausea and vomiting research / Nathalie Percie du Sert and Paul L.R. Andrews -- The ferret in lung carcinogenesis and nutritional chemoprevention research / Xiang-Dong Wang and Chun Liu.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Animal Diseases; Ferrets; Animals, Laboratory; Ferrets as laboratory animals; Ferret; Ferret -- Diseases; TECHNOLOGY & ENGINEERING -- Agriculture -- Animal Husbandry; Ferret; Ferret -- Diseases; Ferrets as laboratory animals; Animal Diseases; Animals, Laboratory; Ferrets; Electronic books